Cephalometric Assessment of Iraqi Sample from Basrah City for Orthodontic and Surgical Treatment Planning - Riad Al-Taee; Aqeel Ibrahim Lazim Al-Saedi; Mohammed Nahidh (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives: The aims of the present study were to establish the cephalometric norms for Iraqi sample fromBasrah city and to study the sexual dimorphism.Materials and Methods: Fifty dental students having normal occlusion were recruited and examinedclinically then digital true lateral cephalometric X-rays were taken and analyzed using Smile streamsoftware. Mean values and standard deviations were obtained and unpaired t-test was applied to assess thegenders difference.Results: Most of the skeleto-dental measurements lie within the normal range with almost proclinedmandibular incisors and no significant gender differences.Conclusions: Assessing the skeleto-dental relationships is far important to arrange accurate diagnosis andtreatment planning for orthodontic and orthognathic cases.